Beyond Tebowing and superstitions: religious practices of 15-year-old competitive athletes. Issue 1 (2nd January 2016) - Hoven, Matt; Kuchera, Samantha
Abstract: Research of religious practices in sport typically limits investigation to Christian prayer and/or "superstitions" among professional or collegiate athletes. This study moves in a different direction by examining the religious spiritual practices reported by 13 adolescent competitive athletes in individual interviews and focus groups. With a mix of religious backgrounds among the 15-year-old participants, this sample of males and females reported religious practices such as talking with dead ancestors and different forms of prayer and meditation. The paper categorises these and other practices according to Nancy Tatom Ammerman's 2014 study, enabling a conceptualisation of how adolescent athletes use religious practices in everyday ways to enable confidence in their play. The study overall points to a significant religious element within competitive youth sports that challenges cynical assumptions about elite athletes' use of religion found in other studies.